2022
DOI: 10.3389/fneur.2022.897275
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Exacerbation of Relapses Following mRNA COVID-19 Vaccination in Multiple Sclerosis: A Case Series

Abstract: IntroductionmRNA coronavirus disease 2019 (COVID-19) vaccination has been widely used to arrest the spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. Rarely, autoimmune events such as relapses in patients with multiple sclerosis (MS) have been reported after vaccination. However, the possible effects of vaccination in a patient already experiencing the symptoms of a relapse represent an unusual scenario that has not been described.Patients and MethodsThis is a retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Each vaccine triggers a different set of signaling pathways. Regarding innate immunity, vector-based vaccines elicit Toll-like receptor (TLR) 9, the major dsDNA sensor, and mRNA vaccines elicit TLR7 and MDA5, the major RNA sensor [ 54 ]. In microglia, macrophages, plasmacytoid dendritic cells, monocytes, and B lymphocytes, TLR 7 (upregulated in experimental autoimmune encephalomyelitis (EAE)) can detect single-stranded RNA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Each vaccine triggers a different set of signaling pathways. Regarding innate immunity, vector-based vaccines elicit Toll-like receptor (TLR) 9, the major dsDNA sensor, and mRNA vaccines elicit TLR7 and MDA5, the major RNA sensor [ 54 ]. In microglia, macrophages, plasmacytoid dendritic cells, monocytes, and B lymphocytes, TLR 7 (upregulated in experimental autoimmune encephalomyelitis (EAE)) can detect single-stranded RNA.…”
Section: Discussionmentioning
confidence: 99%
“…In microglia, macrophages, plasmacytoid dendritic cells, monocytes, and B lymphocytes, TLR 7 (upregulated in experimental autoimmune encephalomyelitis (EAE)) can detect single-stranded RNA. By triggering TLR7, naive T cells are induced to secrete IL-1, IL-6, and IL-12 and differentiate into Th1 and Th17 cells, which may release IL-17 and IFN-gamma [ [54] , [55] ]. Vector-based vaccines activate TLR9 to cause the production of IFN-B, which modulates IL-17 production and suppresses T-cell activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quintanilla-Bordás et al reported a case series of four patients that received mRNA COVID-19 vaccination while already suffering from symptoms related to CNS demyelination due to yet undiagnosed MS [ 66 •]. All of these patients presented with exacerbation of ongoing symptoms after vaccination with MRI features suggestive of highly active MS, fulfilling McDonald 2017 criteria; high serum light-neurofilament levels and oligoclonal bands restricted to the CSF.…”
Section: Covid-19 Vaccination and Pre-existing Or New-onset Cns Demye...mentioning
confidence: 99%